O‘ZBEK TILI OQUV FANINI O`ZIGA XOS ZAMONAVIY METODLAR ASOSIDA TASHKIL ETISHN ZARURIYATLARI - Husaynova Dilafruz; Yandasheva Diliniso (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2021)
This paper makes analyses of the modern methods form Uzbek language subject. On this case, research has been pinpointed from various aspects to get better development in the further. In conclusion, research has been outlined both outcomes and shortcomings of the topic with some suggestions